AN OVERVIEW ON LAND ADMINISTRATION AND MANAGEMENT PROJECTS IN CENTRAL AND EASTERN EUROPE COUNTRIES - Bejtja, Saida; Bejtja, Dritan (European Scientific Journal, ESJ, 2015)
In Central and Eastern Europe countries (CEEC), Land Administration and Management (LAM) has been included within 37 projects, 21 of which were ‘stand-alone’ Land Administration and Management Projects (LAMP). Over US1 billion in loan or credit funds from the Bank has augmented government programs and assistance from bilateral donors in a region that has seen a greater level of land and property redistribution than has been experienced anywhere else in history. The injection of funds through making property assets more liquid and the establishment of effective and efficient property registration systems that have allowed or promoted the introduction of these assets into the economy have been a major factor in the positive economic trends that have been seen in the region. The stage of establishing the initial cadasters and property registration systems in CEEC has been largely successful and there are only a few countries left in the region still lacking this basic infrastructure. The stage is now set for consolidating the gains and building upon the results of these projects. It is estimated that real estate markets may contribute up to 25% of GDP in a developed country, and that the share of global capital stock represented by real estate is about two thirds.